Local Government Supervision of the Circulation of Tuak (Alcoholic) Beverages in the Context of Implementing Public Order, Peace and Community Protection - Muhamad Haiqal Hakiki; Emilda Firdaus; Separen Separen (Pattimura Legal Journal)
Introduction: The circulation of alcoholic beverages in Tembilahan District is a social problem that requires strict supervision from the local government. Based on the Regional Regulation of Indragiri Hilir Regency Number 3 of 2023, supervision of the circulation of alcoholic beverages is the responsibility of the Pamong Praja Police Unit to maintain public order, peace, and community protection.